Electrochemical alumina technology for power electronics devices - D. L. Shimanovich; V. A. Yakovtseva (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The electrochemical alumina technology (ELAT) for the formation of heat-conducting aluminum substrates with a dielectric layer of anodic aluminum oxide with breakdown voltages above 6 kV is discussed. The developed technology can be used in the production of any electronic device operated in the temperature range from 10 to 473 K and frequencies of the gigahertz range.